ANALYSIS OF THE EFFECT OF MIRROR REFLECTORS ON POWER OUTPUT OPTIMIZATION IN FLOATING SOLAR POWER PLANTS - Rocky Torang Silaban; Joko Setiyono (Adisam Publisher, 2025)
Floating Solar Power Plants (FSPP) are a potential renewable energy solution, but their power output is highly influenced by fluctuating solar intensity. This research aims to analyze the optimization of power output in a floating solar power plant with the addition of mirror reflectors. The research method used is experimental, comparing the performance of series-connected solar panels, both without reflectors and with the addition of reflectors at various angles of 30°, 45°, and 60°. Data was collected over four days from 09:00 to 15:00 WIB, including measurements of light intensity, current, and voltage. The results show that the use of mirror reflectors significantly increases power output. The 60° reflector angle yielded the most optimal performance, with the highest light intensity reaching 1210 W/m², a current of 3.90 A, a voltage of 14.22 V, and an input power (Pin) of 349.20 Watts. Although the highest peak output power (Pout) was recorded at the 45° angle (51.76 Watts), the highest average Pout (29.76 Watts) and the highest peak efficiency (23.39%) were achieved with the 60° angle. It is concluded that the addition of a mirror reflector at a 60° angle is the most effective method for optimizing power harvesting in floating solar power plants.